Two new species of Glaphyropyga Schiner (Diptera: Asilidae: Asilinae) from Peru - Sánchez, Pável (Zootaxa, 2024)
Two new species in the strictly Neotropical genus Glaphyropyga Schiner, 1866 are described from Peru; Glaphyropyga andina sp. nov. and Glaphyropyga monticola sp. nov., both from Cuzco, elevating to 14 the number of known species in this genus. A distribution map for the Peruvian species is given and a key to the known species is proposed.